Cellulose-based composite heating fiber and preparation method and application thereof

Through wet coaxial spinning process and two-stage solvent exchange technology, the core-shell structure of cellulose-based composite heating fiber is formed, which solves the problems of poor interface characteristics and insufficient conductivity, and realizes cellulose-based with high mechanical and electrical properties Composite heating fiber, suitable for smart textiles and thermal management fields.

CN119194656AActive Publication Date: 2024-12-27BEIJING FORESTRY UNIVERSITY

Patent Information

Application Number
CN202411478390.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-27
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The existing cellulose-based composite heating fibers have poor interfacial characteristics, limited conductivity, low mechanical strength, and long thermal response time, resulting in insufficient heating and mechanical properties.

Method used

Wet coaxial spinning process is adopted to form a core-shell structure of regenerated cellulose core and nanocellulose/functional material shell through the double-layer extrusion of the inner and outer spinning liquid and two-stage solvent exchange process, thereby improving the mechanical properties of the fibers. and conductivity.

Benefits of technology

It realizes high mechanical properties, excellent electrothermal properties and photothermal properties of cellulose-based composite heating fibers, can quickly reach 195℃ under 6V voltage, and quickly heat up under different lighting conditions. It has simple and easy structure design and is industrialized Production potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194656A_ABST
    Figure CN119194656A_ABST
Patent Text Reader

Abstract

The invention relates to a cellulose-based composite heating fiber as well as a preparation method and application thereof. The cellulose-based composite heating fiber comprises a core formed by regenerated cellulose and a shell formed by a nano cellulose / functional material composite material. The cellulose-based composite heating fiber obtained by the method disclosed by the invention has higher structural integrity and stronger interface bonding capacity, meets excellent mechanical properties, photo-thermal properties and electric heating properties, and has application value in preparation of wearable equipment, heating blankets or physiotherapy equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of functional fibers, cellulose materials, composite fibers, functional fabrics, and thermal management materials, and specifically relates to a cellulose-based composite heating fiber and a preparation method and application thereof. Background Art

[0002] Cellulose-based composite heating fibers are a new type of functional material that is made by combining functional materials with cellulose matrix. In recent years, they have attracted widespread attention in the fields of smart textiles, health care, and thermal management. Cellulose is a natural polymer material that is widely available, inexpensive, and environmentally friendly. Due to its excellent biocompatibility, biodegradability, and mechanical properties, cellulose has been widely used in many fields. In terms of functional material composites, commonly used heating materials include carbon-based materials (such as graphene, carbon nanotubes), metal nanoparticles (such as silver, gold), and conductive polymers (such as polypyrrole, polyaniline), etc. These materials generate heat through different mechanisms (such as electrothermal effect, photothermal effect). Cellulose-based composite heating fibers can generate heat under external electric field or light stimulation, and have good flexibility and mechanical properties. They can be widely used in smart clothing, heating blankets, and physical therapy equipment. In addition, cellulose-based composite heating fibers also have significant advantages in environmental protection and sustainable development, because their main raw materials come from renewable resources and can be degraded or recycled after the end of their service life.

[0003] There are two main methods for preparing cellulose-based composite heating fibers: one is to dissolve cellulose in a solvent and then compound it with a heating material to prepare a composite fiber by wet spinning technology; the other is to prepare cellulose into nanocellulose, then mix it evenly with the heating material to obtain a composite dispersion, and finally prepare the composite fiber by wet spinning technology. However, the following technical problems still exist in the prior art: functional materials such as carbon nanotubes are easy to aggregate, resulting in poor interface properties with the cellulose matrix. If functional groups are introduced on the surface of the heating material or physical adsorption and coating are performed, the compatibility and stability between the dispersion solvents can be improved, but the steps are cumbersome and the method is complicated. Carbon nanotubes are brittle in themselves, and most carbon nanotube dispersions have poor spinnability. Therefore, the carbon nanotube limit content accounts for a small proportion, the conductive performance is limited, and the mechanical strength of the fiber is low. Composite conductive fibers have problems such as single-drive conversion, low thermal conversion efficiency, and long thermal response time.

[0004] Therefore, there is still a need to develop a new fabric fiber with improved heat-generating performance and a preparation method thereof to solve part or all of the above technical problems. Summary of the invention

[0005] Technical Purpose

[0006] The technical purpose of the present invention is to provide a cellulose-based composite heating fiber with improved mechanical properties and heating properties, and a preparation method and application thereof.

[0007] Technical Solution

[0008] In one aspect, the present invention provides a method for preparing a cellulose-based composite heating fiber, comprising the following steps:

[0009] S1: Spinning solution preparation

[0010] S1-1: Preparation of cellulose spinning solution

[0011] The cellulose raw material is completely dissolved in a cellulose solvent, and an auxiliary agent is optionally added according to the dissolution condition and solid content requirements to obtain a cellulose spinning solution;

[0012] S1-2: Preparation of nanocellulose / functional material composite spinning solution

[0013] The nanocellulose and the functional material are mixed and dispersed in deionized water to obtain a nanocellulose / functional material composite spinning solution.

[0014] S2: Wet spinning

[0015] A spinning solution extrusion device equipped with a barrel and a coaxial spinning needle with inner and outer double layers is used to extrude a cellulose spinning solution from the inner layer of the coaxial spinning needle, and a nanocellulose / functional material composite spinning solution is extruded from the outer layer of the needle. The extrusion speeds of the inner and outer spinning solutions are controlled so that the two spinning solutions are extruded simultaneously, and after passing through an air gap with a height of 2-8 cm, they enter a coagulation bath, and wet composite fibers are obtained through a solvent exchange process.

[0016] S3: Solvent exchange and drying

[0017] The wet composite fiber obtained in S2 is placed in the solvent of the coagulation bath and allowed to stand for more than 24 hours, or is wound and moved through the coagulation bath multiple times to allow sufficient solvent exchange to occur between the wet composite fiber and the solvent of the coagulation bath, followed by continuous drying or intermittent drying in an oven, and finally wound on a wire roller to obtain a cellulose-based composite heat-generating fiber, which includes a core composed of regenerated cellulose and a shell composed of a nanocellulose / functional material composite material.

[0018] In a specific embodiment, in step S1-1, the cellulose raw material is first pre-prepared in the following manner: it is broken into small pieces by a paper shredder, and then broken up by a high-intensity cutting machine to facilitate the subsequent acceleration of the dissolution process. The dissolution conditions (temperature, rotation speed, dissolution time, and amount of additives added, etc.) are adjusted according to the dissolution concentration and the dissolution characteristics to improve the spinnability. The cellulose solvent gradually destroys the hydrogen bond network of cellulose, so that the cellulose raw material is completely dissolved in the cellulose solvent to obtain a cellulose spinning solution. The cellulose spinning solution of the inner layer can well impart excellent mechanical strength to the fiber, and at the same time, the fluidity of the nanocellulose / functional material composite spinning solution of the outer layer can drive the flow of the high-viscosity cellulose spinning solution of the inner layer, so that the inner and outer layers are spun out at the same time, forming a continuous spinning process.

[0019] In a specific embodiment, in step S1-1, the cellulose solvent is selected from one or more of an ionic liquid and an N-methylmorpholine oxide (NMMO) solution.

[0020] In a specific embodiment, the ionic liquid is selected from one of superbase ionic liquids, imidazolium ionic liquids, pyridinium ionic liquids and choline ionic liquids, for example, the ionic liquid is 1-allyl-3-methylimidazolium chloride or N-propenylpyridinium chloride.

[0021] The concentration of NMMO solution is 60-80%.

[0022] In a specific embodiment, in step S1-1, the cellulose raw material is selected from one or more of cotton, dissolving wood pulp, refined cotton, and chemical wood pulp, and is in powder or cotton form, and has a degree of polymerization of 400 to 1500.

[0023] In a specific embodiment, in step S1-1, the auxiliary agent is selected from one or more of anhydrous ethanol, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), and N,N-dimethylacetamide (DMAC).

[0024] In a specific embodiment, in step S1-1, the cellulose raw material and the cellulose solvent are mixed in a mass ratio of 1:50-1:15, the mass ratio of the cellulose solvent to the additive is 1:0-1:1, and the total concentration of the cellulose spinning solution is 2-10wt%.

[0025] In a specific embodiment, in step S1-1, the conditions for dissolving the cellulose raw material are: stirring at 60-100°C and 100-800 rpm for 1-5 hours until the cellulose raw material is completely dissolved in the cellulose solvent.

[0026] In a specific embodiment, in step S1-2, the nanocellulose is selected from one or more of unmodified cellulose nanofibrils, TEMPO-oxidized cellulose nanofibrils and carboxymethylated cellulose nanofibrils.

[0027] In a specific embodiment, in step S1-2, the functional material is selected from one of carbon nanotubes, graphene and MXene.

[0028] In a specific embodiment, in step S1-2, the nanocellulose, functional material and deionized water are maintained under a high-speed shearing condition of 300-1000 rpm for 30 min-2 h to be completely and evenly dispersed in the deionized water.

[0029] In a specific embodiment, in step S1-2, the nanocellulose and the functional material are mixed in a mass ratio of 1:0.1-1:10, and the total concentration of the nanocellulose / functional material composite spinning solution is 0.5wt%-5wt%.

[0030] In a specific embodiment, in step S2, the air gap height is 3-8cm, preferably 4cm or 5cm. When the fiber passes through the air gap stage, the dissolved cellulose inside exists in molecular form, and the interaction between the cellulose solvent and the water in the outer spinning solution causes the outer water to gradually enter the interior for solvent replacement, so that a regeneration process occurs inside to form regenerated cellulose. The nanocellulose in part of the outer spinning solution is also exchanged into the inner layer along with the water. At this time, the cellulose chains not only form strong intermolecular interactions with each other, but also interact with the nanocellulose on the contact surface. At the same time, due to the good dispersion between the functional material and the nanocellulose, a small part of the functional material will also enter the inner layer, which is the first-stage solvent exchange process.

[0031] In a specific embodiment, in step S2, the cellulose spinning solution prepared in S1-1 is used as the inner spinning solution, and the nanocellulose / functional material composite spinning solution prepared in S1-2 is used as the outer spinning solution.

[0032] In a specific implementation, in step S2, a feeding device is used to control the extrusion speed of the inner and outer layer spinning solutions, wherein the feeding device can be a gear pump, a vacuum pump, a peristaltic pump, an injection pump, etc., and the feeding device can be selected according to the total amount of the spinning solution.

[0033] In a specific implementation, in step S2, the spinning needles (inner and outer double layers) are one of 10G-32G respectively, and the inner and outer needle specifications can be selected according to the fiber diameter required for actual production and the ratio of the inner and outer diameters.

[0034] In a specific implementation, in step S2, the extrusion speed is 0.06-0.4 ml / min, which is selected according to the rheological properties and solid content of different spinning solutions.

[0035] In a specific embodiment, in step S2, the extrusion temperature is 25-100°C, and the temperature can be controlled by a temperature regulating device of the barrel, and the extrusion temperature is selected according to the rheological properties of the spinning solution.

[0036] In a specific embodiment, in step S2, the solvent of the coagulation bath is selected from one of ethanol, methanol, isopropanol, ethylene glycol and n-butanol.

[0037] In a specific embodiment, in step S2, the solvent exchange is a two-stage solvent exchange as follows: the first-stage solvent exchange process is a process of solvent replacement of the cellulose dissolved in the inner spinning solution and the water in the outer spinning solution; the second-stage solvent exchange process is a process in which the cellulose solvent that has been exchanged into the outer layer is replaced into the coagulation bath, and the water in the fiber is also continuously replaced into the coagulation bath. After passing through the air gap (i.e., the first-stage solvent exchange process), the second-stage solvent exchange is then performed, and the cellulose solvent that has been exchanged into the outer layer is replaced into the coagulation bath, and the water in the fiber is also continuously replaced into the coagulation bath, so that the inner and outer layer interfaces of the regenerated fiber are actually partially interlocked, so that the inner and outer layer components of the fiber can be solidified and formed at the same time, so that the core-shell fiber is more tightly combined, and the tightly connected interface between the core and the shell prevents the outer shell from falling off, which is more conducive to the formation of a stable structure of the composite fiber. When all the cellulose solvent and water are replaced into the coagulation bath, a stable gel-like fiber will be formed. In addition, the smaller surface tension of the coagulation bath makes the fiber surface rough and porous. This rough structure can increase the contact area of ​​the fiber, which helps to improve the photothermal performance, thereby enabling the composite fiber to have high orientation, high conductivity and high light absorption.

[0038] In a specific embodiment, in step S3, continuous drying is performed by an online device or intermittent drying is performed in an oven.

[0039] On the other hand, the present invention provides a cellulose-based composite heat-generating fiber, the cellulose-based composite heat-generating fiber comprising:

[0040] a core composed of regenerated cellulose; and

[0041] Shell composed of nanocellulose / functional material composites.

[0042] In a specific embodiment, the regenerated cellulose is formed by dissolving and regenerating one or more cellulose raw materials selected from cotton, dissolving wood pulp, refined cotton, and chemical wood pulp.

[0043] In a specific embodiment, in the nanocellulose / functional material composite material, the nanocellulose is selected from one or more of unmodified cellulose nanofibrils, TEMPO oxidized cellulose nanofibrils and carboxymethylated cellulose nanofibrils; and the functional material is selected from one of carbon nanotubes, graphene and MXene.

[0044] In a specific embodiment, the cellulose-based composite heating fiber is prepared by the above method.

[0045] The cellulose-based composite heating fiber of the present invention has good mechanical properties. It can not only stretch with the rubber band, but also withstand a certain degree of bending and swinging, and lift a weight (200g) that is 2000 times its own weight. At the same time, the cellulose-based composite heating fiber of the present invention has excellent electrothermal properties due to the addition of functional materials in the outer layer. It can quickly reach 195°C at a voltage of 6V, and has good electrothermal responsiveness and recyclability. In addition, the rough surface structure of the cellulose-based composite heating fiber of the present invention gives it good photothermal properties, at 100mW / cm 2 , 200mW / cm 2 and 300mW / cm 2 Under the power density lighting conditions, the cellulose-based composite heating fiber can heat up from room temperature to 40℃, 49℃ and 73℃ within 180s.

[0046] On the other hand, the present invention provides a product, which at least comprises the above-mentioned cellulose-based composite heat-generating fiber.

[0047] In specific embodiments, the article is a wearable device, a heating blanket, or a physical therapy device.

[0048] In a specific embodiment, the article is clothing, shoes, or headwear.

[0049] Beneficial Effects

[0050] 1. The present invention prepares cellulose-based composite heating fibers by two-stage solvent replacement of air and coagulation bath, optimizing the wet coaxial spinning process and structural design. Compared with the fibers prepared by traditional dipping or spraying, the core-shell structured fibers can obtain higher structural integrity and stronger interface bonding ability by only physical methods. The preparation method is simple and easy, has the potential for continuous production, and is expected to be industrially produced.

[0051] 2. The cellulose-based composite heating fiber designed by the present invention not only retains the high strength and excellent toughness of regenerated cellulose, but also overcomes the disadvantage of poor spinnability of regenerated cellulose. Nanocellulose and functional materials are introduced into the outer layer to give the fiber electrothermal and photothermal properties. The prepared fiber simultaneously meets excellent mechanical properties, photothermal properties and electrothermal properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The side surface SEM image of the composite heat-generating fiber prepared in Example 1 of the present invention is shown.

[0053] Figure 2 Shown is a transverse cross-sectional SEM image of the composite heat-generating fiber prepared in Example 1 of the present invention.

[0054] Figure 3 The SEM image of the outer layer structure of the composite heat-generating fiber prepared in Example 1 of the present invention is shown.

[0055] Figure 4 A diagram showing the mutual stretching of the composite heating fiber and the rubber band prepared in Example 1 of the present invention.

[0056] Figure 5 The swing (a) and bending (b) diagrams of the composite heat-generating fiber prepared in Example 1 of the present invention are shown.

[0057] Figure 6 A graph showing the composite heat-generating fiber prepared in Example 1 of the present invention lifting a 200g weight.

[0058] Figure 7 The temperature variation curve of the composite heating fiber prepared in Example 2 of the present invention under different voltages is shown.

[0059] Figure 8 The temperature variation curve of the composite heating fiber prepared in Example 2 of the present invention in five cycles under a voltage of 6V is shown.

[0060] Fig. 9 The temperature variation curve of the composite heating fiber prepared in Example 3 of the present invention under different light intensities is shown.

[0061] Fig.10 The rheological diagrams of the spinning solutions prepared in Example 2 of the present invention and Comparative Example 1 are shown.

[0062] Fig.11 A photograph of the fiber prepared in Comparative Example 1 of the present invention is shown.

[0063] Fig.12 A photograph of the fiber prepared in Comparative Example 2 of the present invention is shown.

[0064] Fig.13 A photograph of the fiber prepared in Comparative Example 3 of the present invention is shown.

[0065] Fig.14 A photograph of the fiber prepared in Comparative Example 4 of the present invention is shown. DETAILED DESCRIPTION

[0066] The technical solution of the present application is described in detail below through examples so that those skilled in the art can better understand the present invention. However, these examples are not intended to limit the scope of the present application.

[0067] the term

[0068] In the present application, ranges shown with numbers are intended to include all integers and decimal points between the lower value and the upper value in the range.

[0069] Example 1

[0070] (S)1 Preparation of spinning solution:

[0071] (S1-1) Preparation of cellulose spinning solution: First, refined cotton with a degree of polymerization of 600 is shredded into small pieces by a shredder, and then shredded into cotton-like pieces by a high-intensity cutter. Then, the refined cotton and N-methylmorpholine oxide (NMMO) solution are mixed at a mass ratio of 1:20, and dissolved at 100° C. and 200 rpm for at least 2 hours to obtain a cellulose spinning solution with a concentration of 5%.

[0072] (S1-2) Preparation of nanocellulose / functional material composite spinning solution: Carboxymethylated cellulose nanofibrils: graphene were added into deionized water at a mass ratio of 6:1 to make the total concentration 1.2%. The solution was kept at a high shearing speed of 500 rpm for 30 minutes to be completely and evenly dispersed in the deionized water.

[0073] (S2) Wet spinning: Wet spinning was performed using a spinning solution extrusion device equipped with a barrel and a coaxial spinning needle (inner and outer double layers), with the cellulose spinning solution prepared in (S1-1) as the inner layer and the nanocellulose / functional material composite spinning solution prepared in (S1-2) as the outer layer. The inner and outer coaxial spinning needles were 21G (outer diameter 0.81mm, inner diameter 0.51mm) and 16G (outer diameter 1.65mm, inner diameter 1.19mm), respectively. The spinning speeds of the inner and outer injection pumps were 0.07ml / min and 0.35ml / min, respectively. The temperature of the inner layer was controlled to 70°C by the barrel's temperature control device, so that the inner and outer spinning solutions were extruded simultaneously. The syringe and the anhydrous ethanol coagulation bath liquid level were 5cm, and the fiber entered the coagulation bath after passing through an air gap.

[0074] (S3) Solvent exchange and drying: The wet composite fiber obtained in (S2) is wound and moved through a n-butanol coagulation bath to allow sufficient solvent exchange to occur between the wet composite fiber and the solvent of the coagulation bath, followed by intermittent drying in an oven, and finally wound on a wire roller to obtain a cellulose-based composite heat-generating fiber, which structurally includes a core composed of regenerated cellulose and a shell composed of a nanocellulose / functional material composite material.

[0075] The cellulose-based composite heating fiber prepared above was observed by SEM and a series of mechanical property tests were performed, and the results are as follows. Figure 1 and Figure 2 The side surface SEM image and cross-sectional SEM image of the cellulose-based composite heating fiber prepared in Example 1 are shown respectively. Figure 3 The SEM image of the outer layer of the cellulose-based composite heating fiber is shown. It can be clearly seen that the fiber presents a rough and porous core-shell structure, and the interface is tightly connected. The inner layer is a solid and dense structure, and the outer layer is highly oriented along the direction of fiber formation ( Figure 2 and Figure 3 The excellent mechanical strength of cellulose is well endowed to the cellulose-based composite heating fiber. The fiber can not only stretch with the rubber band ( Figure 4 ), and can withstand a certain degree of swing and bending ( Figure 5 ). It can also lift objects 2000 times its own weight (200g) without breaking ( Figure 6 ).

[0076] Example 2

[0077] (S1) Preparation of spinning solution:

[0078] (S1-1) Preparation of cellulose spinning solution: First, dissolving wood pulp with a degree of polymerization of 800 is shredded into small pieces by a paper shredder, and then shredded into cotton-like pieces by a high-intensity cutter. Then, the dissolving wood pulp and 1-allyl-3-methylimidazolium chloride are mixed in a mass ratio of 1:25, and dissolved at 80°C and 100 rpm for at least 2 hours, and then a dimethyl sulfoxide solution with a mass ratio of 1:1 to the ionic liquid is added, and the mixture is reacted at 80°C and 100 rpm for at least 4 hours to obtain a cellulose spinning solution with a concentration of 4%.

[0079] (S1-2) Preparation of nanocellulose / functional material composite spinning solution: TEMPO (2,2,6,6-tetramethylpiperidine-1-oxide) oxidized cellulose nanofibrils: carbon nanotubes were added to deionized water at a mass ratio of 7:1 to make a total concentration of 1%. The solution was kept at a high shearing condition of 500 rpm for 30 minutes to be completely and evenly dispersed in the deionized water.

[0080] (S2) Wet spinning: Wet spinning was performed using a spinning solution extrusion device equipped with a barrel and a coaxial spinning needle (inner and outer double layers), with the cellulose spinning solution prepared in (S1-1) as the inner layer and the nanocellulose / functional material composite spinning solution prepared in (S1-2) as the outer layer. The inner and outer coaxial spinning needles were 21G (outer diameter 0.81mm, inner diameter 0.51mm) and 16G (outer diameter 1.65mm, inner diameter 1.19mm), respectively. The vacuum pump spinning speeds of the inner and outer layers were 0.09ml / min and 0.28ml / min, respectively. The temperature of the inner layer was controlled to 60°C by the barrel's temperature control device, so that the inner and outer spinning solutions were extruded simultaneously. The syringe and the anhydrous ethanol coagulation bath liquid level were 4cm, and the fiber entered the coagulation bath after passing through an air gap.

[0081] (S3) Solvent exchange and drying: The wet composite fiber obtained in (S2) is placed in an anhydrous ethanol coagulation bath with a liquid level sufficient to cover the fiber and allowed to stand for more than 24 hours to allow sufficient solvent exchange to occur between the wet composite fiber and the solvent in the coagulation bath. The fiber is then continuously dried through an online device and finally wound on a wire roller to obtain a cellulose-based composite heat-generating fiber.

[0082] The electrothermal performance of the cellulose-based composite heating fiber obtained above was tested: 1.5 cm of the composite fiber was cut, a voltage controller (WPS3010B) was used to control the voltage at both ends of the sample, and an infrared thermal imager (fotric325Pro) was used to measure the real-time temperature of the fiber and collect data.

[0083] The results are as follows Figure 7 shown. Figure 7 The temperature of the fiber of this embodiment at different voltages is shown. At 2V and 6V, the temperature of the fiber can reach about 40 and 195°C, respectively. And under 5 cycles of applying and releasing 6V voltage, the fiber shows fast electrothermal responsiveness and cyclic repeatability ( Figure 8 ). The above results confirm that the structural design of the cellulose-based composite heating fiber makes the fiber have excellent electrothermal performance, which is of great significance to the fields of human thermal management, medical care, etc. The fiber has a unique core-shell structure. The rich cellulose in the inner and outer layers gives the fiber good mechanical properties. The functional material in the outer layer forms a porous conductive network in the outer layer of the fiber, making the fiber conductive, thus giving it good electrothermal performance.

[0084] Example 3

[0085] (S1) Preparation of spinning solution:

[0086] (S1-1) Preparation of cellulose spinning solution: First, chemical wood pulp with a degree of polymerization of 1000 is shredded into small pieces by a shredder, and then shredded into cotton-like pieces by a high-intensity cutter. Then, chemical wood pulp and N-acrylpyridinium chloride are mixed in a mass ratio of 1:20, and dissolved at 90°C and 150 rpm for at least 3 hours, and then a dimethyl sulfoxide solution with a mass ratio of 1:0.5 to the ionic liquid is added, and the mixture is reacted at 90°C and 150 rpm for at least 5 hours to obtain a cellulose spinning solution with a concentration of 3.3%.

[0087] (S1-2) Preparation of nanocellulose / functional material composite spinning solution: TEMPO oxidized cellulose nanofibrils: carbon nanotubes were added into deionized water at a mass ratio of 9:1 to make the total concentration 2%. The solution was kept at a high shearing rate of 600 rpm for 30 minutes to be completely and evenly dispersed in the deionized water.

[0088] Steps (S2) and (S3) are the same as those in Example 2.

[0089] The photothermal performance of the cellulose-based composite heating fiber obtained above was tested: a spectroradiometer (CEL-NP2000.CeAulight·China) was placed in the illumination center of a xenon lamp (CEL-HXUV300, CeAulight·China) with an AM·1.5·G filter to test the light intensity, and then 1.5 cm of the composite fiber was cut and overlapped and placed in the illumination center, and an infrared thermal imager (fotric325Pro) was used to measure the real-time temperature of the fiber and collect data.

[0090] The results are as follows Fig. 9 As shown, at a power density of 100mW / cm 2 , 200mW / cm 2 and 300mW / cm 2 The temperature of the fiber rises from 30°C to 40°C, 49°C and 73°C respectively within 180s. The above results confirm that by optimizing the spinning process and structural design, the rough and porous surface structure of the fiber is used to effectively increase the contact area with light and heat, so that the fiber provides more photon absorption cross-sections, thus showing strong photothermal performance.

[0091] Comparative Example 1

[0092] (S1) Preparation of spinning solution:

[0093] Preparation of cellulose spinning solution: First, dissolving wood pulp with a degree of polymerization of 800 is shredded into small pieces by a paper shredder, and then broken into cotton-like pieces by a high-intensity cutter. Then, dissolving wood pulp and 1-allyl-3-methylimidazolium chloride are mixed at a mass ratio of 1:25, and dissolved at 80°C and 100 rpm for at least 2 hours, and then a dimethyl sulfoxide solution with a mass ratio of 1:1 to the ionic liquid is added, and the mixture is reacted at 80°C and 100 rpm for at least 4 hours to obtain a cellulose spinning solution with a concentration of 4%.

[0094] (S2) Wet spinning: The cellulose spinning solution prepared in (S1) was used alone as the spinning solution, and wet spinning was performed using a spinning solution extruder equipped with a barrel and a spinning needle. The spinning needle was 21G (outer diameter 0.81 mm, inner diameter 0.51 mm), the vacuum pump spinning speed was 0.09 ml / min, and the barrel temperature was controlled at 60° C. The distance between the syringe and the anhydrous ethanol coagulation bath liquid level was 5 cm, and the fiber entered the coagulation bath after passing through an air gap.

[0095] Wet spinning requires the spinning solution to have good rheological properties in order to facilitate smooth extrusion. The wet spinning behavior in the above Example 2 and Comparative Example 1 was evaluated, and the results are as follows.

[0096] Fig.10 It shows that the nanocellulose / functional material composite spinning solution in Example 2 exhibits shear thinning behavior, exhibits good fluidity, and is conducive to improving spinnability. However, the cellulose spinning solution in Example 2 and Comparative Example 1, which is the same as that in Comparative Example 1, does not have shear thinning behavior, has a high viscosity, and is difficult to wet spin. Although the subsequent wet spinning process is exactly the same as that in Example 2, Comparative Example 1 cannot achieve continuous fiber ( Fig.11 ), this is because the lack of the high rheological nanocellulose / functional material composite spinning solution of the outer layer cannot drive the cellulose spinning solution of the inner layer to be effectively wet-spun, indicating the importance of the design of the outer layer for the construction of core-shell structure fibers.

[0097] Comparative Example 2

[0098] (S1) Preparation of spinning solution:

[0099] Preparation of nanocellulose / functional material composite spinning solution: Add TEMPO oxidized cellulose nanofibrils to carbon nanotubes at a mass ratio of 7:1 into deionized water to make the total concentration 1%. Maintain the high-speed shearing condition at 500 rpm for 30 minutes to completely and evenly disperse in the deionized water.

[0100] (S2) Wet spinning: The nanocellulose / functional material composite spinning solution prepared in (S1) was used as the spinning solution alone, and wet spinning was performed using a spinning solution extrusion device equipped with a barrel and a spinning needle. The spinning needle was 16G (outer diameter 1.65mm, inner diameter 1.19mm), and the vacuum pump spinning speed was 0.28ml / min. The distance between the syringe and the anhydrous ethanol coagulation bath liquid level was 6cm, and the fiber entered the coagulation bath after passing through an air gap.

[0101] The wet spinning behavior in Comparative Example 2 was evaluated and the results are as follows.

[0102] Although the nanocellulose / functional material composite spinning solution in Comparative Example 2 has good rheological properties, and the subsequent wet spinning process is exactly the same as that in Example 2, it is still impossible to perform continuous spinning alone. The fibers are very easy to break in the coagulation bath due to the lack of good mechanical properties ( Fig.12 ).

[0103] In Example 2, the cellulose spinning solution of the inner layer imparts excellent mechanical properties to the cellulose-based composite heating fiber, which is combined with the high electrothermal and photothermal properties of the nanocellulose / functional material composite spinning solution of the outer layer.

[0104] Comparative Example 3

[0105] (S1) The preparation of the spinning solution is exactly the same as in Example 2.

[0106] (S2) Wet spinning is the same as in Example 2, except that the distance between the syringe outlet and the coagulation bath is adjusted to zero, so that the fiber directly enters the anhydrous ethanol coagulation bath without passing through an air gap.

[0107] The wet spinning behavior in Comparative Example 3 was evaluated, and the results are as follows. The fibers wet-spun from the same spinning solution as in Example 2 did not pass through the air gap stage but directly entered the anhydrous ethanol coagulation bath after exiting the syringe, i.e., there was no first-stage solvent exchange process, only a second-stage solvent exchange process, from Fig.13 It can be seen that after the fiber of Comparative Example 3 enters the coagulation bath, the cellulose spinning solution and the nanocellulose / functional material composite spinning solution are immediately separated into two parts, and a complete single fiber cannot be formed. This confirms the necessity of the first-stage solvent exchange process for spinning.

[0108] Comparative Example 4

[0109] (S1) The preparation of the spinning solution is exactly the same as in Example 2.

[0110] (S2) Wet spinning is the same as in Example 2, except that the distance between the syringe and the anhydrous ethanol coagulation bath liquid level is adjusted to 15 cm, and the fiber enters the coagulation bath after passing through a longer air gap.

[0111] The wet spinning behavior in Comparative Example 4 was evaluated and the results are as follows.

[0112] from Fig.14 It can be seen that the fibers of Comparative Example 4 are beaded. This is because the air gap height is too high, that is, the first-stage solvent exchange process is long, the rheological properties of the inner and outer layers are quite different, and due to gravity, the outer layer of nanocellulose / functional material composite spinning solution cannot drive the flow of the inner layer of high-viscosity cellulose spinning solution in time, thus forming beaded fibers. Comparative Examples 3 and 4 can prove the importance of the two-stage solvent exchange process in this design for the continuous spinning of cellulose-based composite heat-generating fibers.

Claims

1. A method for preparing a cellulose-based composite heating fiber, comprising the following steps: S1: Spinning solution preparation S1-1: Preparation of cellulose spinning solution The cellulose raw material is completely dissolved in a cellulose solvent, and an auxiliary agent is optionally added to obtain a cellulose spinning solution; S1-2: Preparation of nanocellulose / functional material composite spinning solution The nanocellulose and the functional material are mixed and dispersed in deionized water to obtain a nanocellulose / functional material composite spinning solution. S2: Wet spinning A spinning solution extrusion device equipped with a barrel and a coaxial spinning needle with inner and outer double layers is used to extrude a cellulose spinning solution from the inner layer of the coaxial spinning needle, and a nanocellulose / functional material composite spinning solution is extruded from the outer layer of the needle. The extrusion speeds of the inner and outer spinning solutions are controlled so that the two spinning solutions are extruded simultaneously, and after passing through an air gap with a height of 2-8 cm, they enter a coagulation bath, and wet composite fibers are obtained through a solvent exchange process. S3: Solvent exchange and drying The wet composite fiber obtained in S2 is placed in the solvent of the coagulation bath and allowed to stand for more than 24 hours, or is wound and moved through the coagulation bath multiple times to allow sufficient solvent exchange to occur between the wet composite fiber and the solvent of the coagulation bath, followed by continuous drying or intermittent drying in an oven, and finally wound on a wire roller to obtain a cellulose-based composite heat-generating fiber, which includes a core composed of regenerated cellulose and a shell composed of a nanocellulose / functional material composite material.

2. The method according to claim 1, wherein: In step S1-1, The cellulose solvent is selected from one or more of an ionic liquid and an N-methylmorpholine oxide (NMMO) solution, wherein the ionic liquid is selected from one of a superbase ionic liquid, an imidazolyl ionic liquid, a pyridinium ionic liquid and a choline ionic liquid, for example, the ionic liquid is 1-allyl-3-methylimidazolium chloride or N-propenylpyridinium chloride; and / or The cellulose raw material is selected from one or more of cotton, dissolving wood pulp, refined cotton, and chemical wood pulp; and / or The auxiliary agent is selected from one or more of anhydrous ethanol, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), N,N-dimethylacetamide (DMAC); and / or The cellulose raw material and the cellulose solvent are mixed in a mass ratio of 1:50-1:15, the mass ratio of the cellulose solvent to the auxiliary agent is 1:0-1:1, and the total concentration of the cellulose spinning solution is 2-10wt%; and / or The conditions for dissolving the cellulose raw material are: stirring at 60-100° C. and 100-800 rpm for 1-5 hours until the cellulose raw material is completely dissolved in the cellulose solvent.

3. The method according to claim 1, wherein: In step S1-2, The nanocellulose is selected from one or more of unmodified cellulose nanofibrils, TEMPO-oxidized cellulose nanofibrils and carboxymethylated cellulose nanofibrils; and / or The functional material is selected from one of carbon nanotubes, graphene and MXene; and / or The nanocellulose, functional material and deionized water are kept under high-speed shearing conditions of 300-1000 rpm for 30 min-2 h to be completely and evenly dispersed in the deionized water; and / or The nanocellulose and the functional material are mixed in a mass ratio of 1:0.1-1:10, and the total concentration of the nanocellulose / functional material composite spinning solution is 0.5wt%-5wt%.

4. The method according to claim 1, wherein: In step S2, The air gap height is 3-8 cm, preferably 4 cm or 5 cm; and / or The extrusion speed of the inner and outer spinning solutions is controlled by a feeding device, wherein the feeding device is a gear pump, a vacuum pump, a peristaltic pump, or a syringe pump; and / or The spinning needle with inner and outer double layers is one of 10G-32G; and / or The extrusion speed is 0.06-0.4 ml / min; and / or The extrusion temperature is 25-100°C; and / or The solvent of the coagulation bath is selected from one of ethanol, methanol, isopropanol, ethylene glycol and n-butanol.

5. The method according to claim 1, wherein: In step S3, continuous drying is performed by online equipment or intermittent drying in an oven.

6. A cellulose-based composite heat-generating fiber, comprising: a core composed of regenerated cellulose; and Shell composed of nanocellulose / functional material composites.

7. The cellulose-based composite heating fiber according to claim 6, wherein: The regenerated cellulose is formed by dissolving and regenerating one or more cellulose raw materials selected from cotton, dissolving wood pulp, refined cotton, and chemical wood pulp.

8. The cellulose-based composite heating fiber according to claim 6, wherein: The nanocellulose is selected from one or more of unmodified cellulose nanofibrils, TEMPO oxidized cellulose nanofibrils and carboxymethylated cellulose nanofibrils; and the functional material is selected from one of carbon nanotubes, graphene and MXene.

9. The cellulose-based composite heating fiber according to claim 6, which is prepared by the method according to any one of claims 1 to 5.

10. A product comprising at least the cellulose-based composite heating fiber according to any one of claims 6 to 9, for example, the product is a wearable device, a heating blanket or a physiotherapy device.

Citation Information

Patent Citations

  • Protein-based aerogel fiber sound-absorbing material and preparation method thereof

    CN115726053A

  • Binchotan / regenerated cellulose composite fiber and preparation method thereof

    CN118087077A

  • Preparation method of volcanic rock / regenerated cellulose fiber based on coaxial spinning technology

    CN118087078A

  • Method for preparing functional material of regenerated cellulose

    CN1796444A

  • Method for Producing Cellulose multi-filament of industrial usage with Washing Process Characteristic

    KR100769973B1

Cited By

  • Cellulose-based composite phase change fiber as well as preparation method and application thereof

    CN122013359A